Open reduction and internal fixation treatment of distal tibia fracture with Wise lock plate followed by two year follow up - Kumar, Mohit; Rawat, Pooja; Gupta, Jitendra; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2019)
Background: Distal tibial fractures are high energy injuries with high complication rate. The objective of this study was to reduce the postoperative complications of distal tibial fracture by using indigenously manufactured implants (plates and screws). Methods: This was a prospective study of 10 patients (6 patients had 43-B1 fracture, 4 patients had 43-B2 fracture) with two year follow up period followed by physical exercises after one month of the surgery. The fractures were treated with 3.5 mm Wise lock medial distal tibia plate. X-ray was used to check the union, non-union. Functional outcomes were assessed with visual analog scale (VAS) score. Results: X-ray was showing good results. Average VAS score was 1.5 (90%) 9 patients and 2.5 (10%) in 1 patient. At the end of the first year VAS score is 2 for one patient with 9 others having 1 and at the end of the second year the VAS score is 0 for 9 patients and 1 for one patient. Conclusions: Treatment of distal tibial fracture with 3.5 mm Wise lock medial distal tibia plate shows good outcomes with less complications.